Fluctuations in charged particle multiplicities in relativistic heavy-ion collisions. (16th June 2016) - Mukherjee, Maitreyee; Basu, Sumit; Choudhury, Subikash; Nayak, Tapan K
Abstract: Multiplicity distributions of charged particles and their event-by-event fluctuations have been compiled for relativistic heavy-ion collisions from the available experimental data at Brookhaven National Laboratory and CERN and also by the use of an event generator. Multiplicity fluctuations are sensitive to QCD phase transition and to the presence of a critical point in the QCD phase diagram. In addition, multiplicity fluctuations provide baselines for other event-by-event measurements. Multiplicity fluctuation expressed in terms of the scaled variance of the multiplicity distribution is an intensive quantity, but is sensitive to the volume fluctuation of the system. The importance of the choice of narrow centrality bins and the corrections of the centrality bin-width effect for controlling volume fluctuations have been discussed. It is observed that the mean and width of the multiplicity distributions monotonically increase as functions of increasing centrality at all collision energies, whereas the multiplicity fluctuations show minimal variations with centrality. The beam-energy dependence shows that the multiplicity fluctuations have a slow rise at lower collision energies and remain constant at higher energies.